Investigating The Interplay of Community Knowledge, Product Quality, And Islamic Value Adoption in Sharia Banking Savings Decisions - Sari, Desi Ratna; Syah, Toufan Aldian (DAS Institute, 2022)
This study aims to determine the effect of public knowledge, product quality, and interest in applying Islamic values to the decision to use Islamic banking savings. The variables used in this study are decision variables to use Islamic banking savings as the dependent variable and public knowledge, product quality, and interest in applying Islamic values as independent variables. This quantitative research uses primary data, namely data taken directly from the respondents' answers. The number of samples in this study was 100 respondents. The data analysis method used in this study is a multiple linear regression analysis technique. The results of this study indicate that public knowledge and interest in applying Islamic values do not influence the decision to use Islamic banking savings. Moreover, product quality affects the decision to use Islamic banking savings.